Bladder Benign Inverted Papilloma in Young Men: A Case Report - Marrak, Mehdi; Ouanes, Yassine; Chaker, Kays; Rahoui, Moez; Bibi, Mokhtar; Nouira, Yassine (Archives of Case Reports, 2024)
An inverted papilloma of the urinary tract is a rare benign lesion. A 35-year-old male presented gross hematuria. Cystoscopy showed one, papillary tumor at the bladder trigone. Transurethral resection was done, and histological examination has concluded in the diagnosis of inverted papilloma. Following resection, the patient was asymptomatic with no hematuria and no recurrence after a five-year cystoscopy control. We report a case of bladder Inverted papilloma and we aim to remind the clinical, histological, and therapeutic features of this rare tumor.